2021
DOI: 10.1097/nna.0000000000001041
|View full text |Cite
|
Sign up to set email alerts
|

Addiction Nursing Competencies

Abstract: With the increased role of nurses in caring for patients with substance addiction, there was a clear need to develop the Addiction Nursing Competencies to guide and support the nursing workforce. A literature search revealed a lack of formal instruments to assess and guide nurses in caring for persons with substance use disorders. The Addiction Nursing Competencies were created using existing nursing education frameworks and addiction nurse care manager clinical guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…1 To address this, all nurses must have the education and clinical training necessary to care for individuals with substance use disorder. 12 Nurses with education on addiction and possessing well-developed clinical skills in the management of patients with SUD can play a major role in improving the care of this marginalized patient population and reducing negative attitudes toward them. 10 Thus, there is a clear need to establish additional addiction nursing fellowships across the country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 To address this, all nurses must have the education and clinical training necessary to care for individuals with substance use disorder. 12 Nurses with education on addiction and possessing well-developed clinical skills in the management of patients with SUD can play a major role in improving the care of this marginalized patient population and reducing negative attitudes toward them. 10 Thus, there is a clear need to establish additional addiction nursing fellowships across the country.…”
Section: Discussionmentioning
confidence: 99%
“…Selected self-directed learning materials are open-access and cover a range of topics related to nursing care of persons who use substances with an aim to meet, and exceed, the addiction nursing skills and educational competencies as described by Wason et al 12 and Finnell et al 13 Additionally, the curriculum utilizes no-cost and widely accessible remote live and pre-recorded trainings available through the Grayken Center for Addiction Training and Technical Assistance (TTA) program and the Providers Clinical Support System (PCSS). These programs provide free, publicly-available up-to-date, multidisciplinary, evidence-based education, and continuing education units (CEU) for nurses, which can be used to meet the requirement to sit for the CARN examination.…”
Section: Educational Curriculummentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has shown that nurse-led clinics and the expansion of MOUD address critical gaps in these essential services for PWID, particularly in rural areas (Auty et al, 2020;Barnett et al, 2019;Cos et al, 2021;Klein et al, 2022;Sorrell et al, 2020). Additionally, nurses and nurse case managers working in the primary care setting play a critical role in addressing the holistic care needs of patients, including some barriers identified by this review, and can engage PWID in primary care long term (Beharie et al, 2022;Wason et al, 2021).…”
Section: Clinic Al Rele Van Cementioning
confidence: 91%
“…Recent evidence has shown that nurse‐led clinics and the expansion of MOUD address critical gaps in these essential services for PWID, particularly in rural areas (Auty et al, 2020; Barnett et al, 2019; Cos et al, 2021; Klein et al, 2022; Sorrell et al, 2020). Additionally, nurses and nurse case managers working in the primary care setting play a critical role in addressing the holistic care needs of patients, including some barriers identified by this review, and can engage PWID in primary care long term (Beharie et al, 2022; Wason et al, 2021). Overall, nurses in the primary care setting play an important role in addressing barriers to care engagement, improving access to essential substance use and primary care services, and developing meaningful patient–nurse and patient‐care team relationships.…”
Section: Clinical Relevancementioning
confidence: 99%